Analysis of structure borne wave signatures in pipeline leakage detection - Soh, Yan Xin (2013)
The present work is aimed to detect gas leakage on the analysis of structure borne wave. Through acoustic emission, the structure borne wave generated by gas leakage in pipeline could be detected and analysed while in operation. The experiments were carried out using a test rig designed in such a way where three kinds of leakages usually happening in the industries can be imitated and done in the laboratory. The experiments were done on detecting acoustic emission on three different small defects which were thread leakage, pinhole leakage and gasket leakage. It was found experimentally that the slightest leakage would cause acoustic emission to be detected. The detected acoustic emission would increase following the size of the leakage even when the test rig is in operation. In conclusion, acoustic emission is able to detect small leakages of different types. This particular technique can be utilized for greater use in the industry to detect leakage during operation of pipeline.